2015
DOI: 10.5590/ijamt.2015.14.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Conflict Resolution on the Production Line

Abstract: Conflict between coworkers on the production line can be expensive as well as time consuming for companies. The business problem investigated in the study is the inability of supervisors on the production line to resolve conflict in nonunion companies, which, consequently, may lead to a drop in organizational productivity. Behaviors impacting shop floor productivity and performance were detected through miniethnographic and descriptive case study qualitative research methods through research of the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…In a nut shell therefore, constraints related to lack of good leadership and management practices that jeopardised the leaders from effectively managing conflicts include but not necessarily limited to the lack of effective leadership and management skills, leaders' failure to opt for effective management style as well as lack of sound policies and structures for managing conflicts. These challenges correspond well with the existing literatures as formerly discussed in Tanzania and outside Tanzania such as (Brewer, Mitchell et al2002, Rahim 2002, Spaho 2013, Saeed, Almas et al 2014, Fusch and Fusch 2015, Johansen and Cadmus 2016, Rispens, Jehn et al 2020. Wide literature establishes that conflict management is a skill that leaders must be able to employ when needed to help foster a productive working environment (Guttman, 2004).…”
Section: Lack Of Good Leadership and Management Practicessupporting
confidence: 88%
“…In a nut shell therefore, constraints related to lack of good leadership and management practices that jeopardised the leaders from effectively managing conflicts include but not necessarily limited to the lack of effective leadership and management skills, leaders' failure to opt for effective management style as well as lack of sound policies and structures for managing conflicts. These challenges correspond well with the existing literatures as formerly discussed in Tanzania and outside Tanzania such as (Brewer, Mitchell et al2002, Rahim 2002, Spaho 2013, Saeed, Almas et al 2014, Fusch and Fusch 2015, Johansen and Cadmus 2016, Rispens, Jehn et al 2020. Wide literature establishes that conflict management is a skill that leaders must be able to employ when needed to help foster a productive working environment (Guttman, 2004).…”
Section: Lack Of Good Leadership and Management Practicessupporting
confidence: 88%
“…On the other hand, positive conflict arises when confrontation of individuals or groups improves organization's performance, such as improving the quality of decisions, innovation and organizational behavior (Folger et al, 2009;Nawaz & Gomas, 2018;Lee, Avgar, Park & Choi, 2019). Conflict is bound to happened such as between workers in an organization (Fusch, & Fusch, 2015;Douglas, 2012). Conflicts frequent in an organization set up and are associated with the feeling of unfairness, injustice and incompetence of a member or group leader (Tsuno, Kawakami, Inoue, Ishizaki, Tabata, Tsuchiya, Akiyama, Kitazume, Kuroda & Shimazu, 2009), thus a leader's response to conflict can either be helpful or counterproductive (Allan, 2014).…”
Section: Conflictmentioning
confidence: 99%
“…Forster, Patlas, and Lexa (2020), noted that during COVID 19, leader's collaboration and walking with followers is essential in the management of the crises. Moreover, Fusch and Fusch (2015), found that leaders who show respect to followers solved conflict much better while, Jit, Sharma and Kawatra (2016) examination of servant leadership and conflict resolution found that servant leadership characteristic of being patient, composed, and humility is an enabler in conflict management.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…leaders are the key factors that are the responsible for the conflict management and decisions regarding organisation with the power and political leadership skills. (Fush & Fush, 2015). There would be timewasting when the organisational conflicts cannot be managed.…”
Section: Introductionmentioning
confidence: 99%